2019
DOI: 10.1002/elsc.201900058
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation: A biotechnological tool for enhanced production of secondary metabolites in hairy root cultures

Abstract: Elicitation is a possible aid to overcome various difficulties associated with the large‐scale production of most commercially important bioactive secondary metabolites from wild and cultivated plants, undifferentiated or differentiated cultures. Secondary metabolite accumulation in vitro or their efflux in culture medium has been elicited in the undifferentiated or differentiated tissue cultures of several plant species by the application of a low concentration of biotic and abiotic elicitors in the last thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
116
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(142 citation statements)
references
References 90 publications
2
116
0
4
Order By: Relevance
“…Their data also showed that NO quenching suppressed the H 2 O 2 synthesis, and exogenous NO addition increased the H 2 O 2 accumulation, however according to our results, the change of NO concentration had no effect on the H 2 O 2 synthesis. According to the schematic representation of action mode of elicitor in plant cell given by Halder et al [20], NO synthesis was the downstream event of the ROS burst under elicitation, which coincided with our conclusion. These different phenomena and results may be caused by plant species differences or other unknown reasons, and further studies are still needed.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Their data also showed that NO quenching suppressed the H 2 O 2 synthesis, and exogenous NO addition increased the H 2 O 2 accumulation, however according to our results, the change of NO concentration had no effect on the H 2 O 2 synthesis. According to the schematic representation of action mode of elicitor in plant cell given by Halder et al [20], NO synthesis was the downstream event of the ROS burst under elicitation, which coincided with our conclusion. These different phenomena and results may be caused by plant species differences or other unknown reasons, and further studies are still needed.…”
Section: Discussionsupporting
confidence: 92%
“…Elicitation is one of the most effective ways to stimulate the secondary metabolite synthesis in the plant cell, and therefore is now widely employed to induce novel metabolites or enhance the accumulation of the target metabolites in the plant cell, tissue and organ cultures [20]. According to chemical property, the elicitors are normally classi ed into two types, including abiotic elicitors (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of pharmaceutical proteins for therapeutic use is currently in different phases of clinical trials [32]. It is also possible to produce secondary metabolites with high yields using routine techniques of in vitro plant cell and tissue cultures, which are becoming an attractive alternative to traditionally-used, naturally occurring plant material [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…One of the sources of secondary metabolites is the hairy roots culture, the growth of which is initiated by the transfer of the Rol gene of the soil bacterium Agrobacterium rhizogenes to the plant cell genome (Bensaddek et al, 2008;Ono and Tian, 2011;Vladimirov et al, 2015;Dhiman et al, 2018). The root culture obtained in this way has genetic and biochemical stability, unlimited growth rate in growth regulator-free media, short doubling times, high biosynthetic activity and responsiveness to elicitor treatments as well as ecological purity of the plant raw materials (Vdovichenko et al, 2007;Kuzovkina and Vdovichenko, 2011;Khan et al, 2018;Halder et al, 2019). Over the past decades, there was a lot of data on the development of effective protocols for inducing hairy root cultures that can synthesize biologically active substances (Giri et al, 2001;Saleh and Thuc, 2009;Saravanakumar et al, 2012;Farag and Kayser, 2015;Belabbassi et al, 2016;Patra and Srivastava, 2016).…”
Section: Introductionmentioning
confidence: 99%